Attention Process Training-3 to improve reading comprehension in mild aphasia: A single-case experimental design study. Issue 3 (15th March 2020) - Lee, Jaime B.; Sohlberg, McKay Moore; Harn, Beth; Horner, Robert; Cherney, Leora R.
ABSTRACT: People with aphasia frequently present with nonlinguistic deficits, in addition to their compromised language abilities, which may contribute to their problems with reading comprehension. Treatment of attention, working memory and executive control may improve reading comprehension in individuals with aphasia, particularly those with mild reading problems. This single-case experimental design study evaluated the efficacy of Attention Process Training-3, an intervention combining direct attention training and metacognitive facilitation, for improving reading comprehension in individuals with mild aphasia. A multiple baseline design across six participants was used to evaluate treatment effects. The primary outcome measure was a maze reading task. Cognitive measures were administered pre- and post-treatment. Visual inspection of graphed maze reading performance data indicated a basic effect between APT-3 and improved maze reading for three of the six participants. Quantitative analyses, using Tau-U, corroborated findings identified through visual analysis. The overall effect size was significant (Tau = .48, p  = .01). Results suggest that APT-3 has the potential to improve reading in individuals with aphasia, but that it may be more efficacious under certain conditions. Treatment and participant variables, including intensity of treatment and metacognitive strategy usage, are discussed as potential influences on participants' responsiveness to APT-3.